Weighted Window for TCP Fair Bandwidth Allocation in Wireless Lans - Seyedzadegan, Mojtaba (2008)
The explosive growth of the Internet has extended to the wireless domain. The number of Internet users and mobile devices with wireless Internet access is continuously increasing. However, the network resource is essentially limited, and fair service is a key issue in bandwidth allocation. The main objective of this research is to provide fair service in terms of throughput among wireless stations using the TCP window size according to Access Point (AP) queue size for fair bandwidth allocation in wireless LANs. In the first part of this research the focus is on the issue of fairness among stations having different numbers and directions of flow. It is shown in this part that the current WLANs allocate bandwidth unfairly. It is also identified that the cause of this unfairness problem is TCP cumulative ACK mechanism combined with the packet dropping mechanism of AP queue and the irregular space for each station in AP queue. The proposed method allocates converged bandwidth by introducing weighted window method which adjusts the TCP window size based on the current conditions of the network. Therefore, this method works in wireless nodes without requiring any modification in MAC. The second part dealt with the fair bandwidth allocation problem for different required bandwidth which aims to improve weighted window method to assure fair channel is fairly shared between wireless nodes in the same class of bandwidth. The proposed class-based weighted window method adjusts the TCP window size of each station according to their weights. So the stations share the wireless channel fairly in terms of throughput. The proposed methods can guarantee fair service in terms of throughput among wireless users either they require the same or different bandwidth.